Numerical studies on the parasitic modes in gyrotron beam tunnels - Latsas, G. P.; Ioannidis, Z. C.; Tigelis, I. G. (Plasma Science (ICOPS), 2011 Abstracts IEEE International Conference on, 2011)
Summary form only given. Megawatt gyrotrons are found to suffer from various RF oscillations in the beam tunnel prior to the desired interaction zone (the cavity). The development of such parasitics degrades the beam quality reducing the efficiency of the cyclotron interaction and the overall produced power. Furthermore, it affects the stability of operation. Several design approaches have been implemented in order to suppress the parasitic modes; most of them involve the increase of the dissipation in the beam tunnel by means of lossy ceramic materials. However, despite the increased losses, parasitic oscillations still appear in several new designs, especially when the produced power and/or operating frequency is increased. In this work, we employ the numerical code FISHBONE, as well as the commercial simulation software CST STUDIO SUITE in order to study the parasitic modes which appear in a gyrotron beam tunnel. Furthermore, the effect of the geometry of the structure as well as the various design parameters on the parasitic modes is studied, in order to identify the origin and properties of the parasitic oscillations.
Keywords: beam quality; cyclotron interaction efficiency; design approaches; design parameters; gyrotron beam tunnels; gyrotrons; interaction zone; lossy ceramic materials; megawatt gyrotrons; numerical code FISHBONE; operating frequency; operation stability; overall produced power; parasitic modes; parasitic oscillation properties; plasma oscillations; plasma simulation; RF oscillations; simulation software CST STUDIO SUITE